The Influence of Work Culture and Work Environment on Organizational Commitment in The Bureau of Institutions and Implementation of The Main Staff for General Planning and Budget of The State Police Republic of Indonesia - Mila Cahyani; Harries Madiistriyatno; Widya Nengsih (Dinasti Publisher, 2026)
The purpose of this study is to determine and analyze the influence of work culture on organizational commitment, to determine and analyze the influence of work environment on organizational commitment, to determine and analyze the influence of work culture and work environment simultaneously on organizational commitment, the calculated t value for the Work Culture variable (X1) is 4,726, while the ttable value for N = 64 is 1,997. So 4,726 > 1,997, then H0 is rejected and Ha is accepted, it can be stated that Work Culture (X1) has a significant effect on Organizational Commitment (Y), the calculated t value for the Work Ability variable (X2) is 8,899, while the ttable value for N = 64 is 1,997. So 8,899 > 1,997, then Ho is rejected and Ha is accepted, it can be concluded that partially the Work Ability variable (X2) has an effect on Organizational Commitment (Y). The R Square value (R2) is 0,775. This shows that 77,5% Work Culture (X1) and Work Ability (X2) jointly influence Organizational Commitment (Y), while the remainder is 22,5% influenced by other factors not examined in this study.